2020
DOI: 10.1111/ecpo.12171
|View full text |Cite
|
Sign up to set email alerts
|

Female politicians in municipal councils and fiscal performance

Abstract: Empirical research has tried to explain the effect of female politicians on various outcomes of political institutions. Few studies have focused on how the gender of politicians may affect institutional fiscal performance. Our research shows that both a female mayor, although with limited effect, and a greater share of female councillors worsen the fiscal performance of Spanish municipalities, which contrasts with the hypotheses raised, which were based on the mainstream of theoretical literature. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 130 publications
0
1
0
Order By: Relevance
“…Indeed, the results showed that an influence of the mayor's gender on the level of municipal debt emerges in the model that incorporates all possible effects (2), both direct and moderating, and using both diversity indexes. In the estimates that include the Blau index, the level of debt is 27.02 euros per capita lower (p. <0.01) in the municipalities led by female mayors, in line with the research carried out in Spain by Balaguer-Coll and Toneva (2019), and the recent study by Cuadrado-Ballesteros et al (2024) on municipalities with more than 50,000 inhabitants, and contrary to the findings of Cabaleiro-Casal and Buch-G omez (2021) in the same country and Suzuki and Avellaneda (2018) in Japan, who did not find any evidence of a significant relationship between having a female mayor and the level of municipal debt. This clear effect of the female mayor's gender in reducing municipal debt seems to verify the arguments for lower debt preferences by the female gender (Dohmen et al, 2011;Huang and Kisgen, 2013;Krogstrup and W€ alti, 2011).…”
Section: Findings and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Indeed, the results showed that an influence of the mayor's gender on the level of municipal debt emerges in the model that incorporates all possible effects (2), both direct and moderating, and using both diversity indexes. In the estimates that include the Blau index, the level of debt is 27.02 euros per capita lower (p. <0.01) in the municipalities led by female mayors, in line with the research carried out in Spain by Balaguer-Coll and Toneva (2019), and the recent study by Cuadrado-Ballesteros et al (2024) on municipalities with more than 50,000 inhabitants, and contrary to the findings of Cabaleiro-Casal and Buch-G omez (2021) in the same country and Suzuki and Avellaneda (2018) in Japan, who did not find any evidence of a significant relationship between having a female mayor and the level of municipal debt. This clear effect of the female mayor's gender in reducing municipal debt seems to verify the arguments for lower debt preferences by the female gender (Dohmen et al, 2011;Huang and Kisgen, 2013;Krogstrup and W€ alti, 2011).…”
Section: Findings and Discussionsupporting
confidence: 84%
“…Moreover, the fact that we have found weaker significant effects of gender diversity on municipal indebtedness in the first model than in the second model may be explained because the intergroup bias engendered by other factors seem to prevent visualizing the effects of diversity (van Knippenberg and Schippers, 2007). In contrast, the estimates with the indicator of the percentage of women in the government teamthe bias approachdo not allow us to visualize any effect on municipal debt in either of the two models, which is in line with recent research by Balaguer-Coll and Toneva (2019), Cabaleiro-Casal and Buch-G omez (2021) and Cuadrado-Ballesteros et al (2024), and furthermore seems to show evidence of the underlying differences between the concepts of diversity and gender bias. Therefore, these findings seem to endorse our arguments that the marked gender differences in budget preferences (Alesina and La Ferrara, 2005;Alvarez and McCaffery, 2003;Geys and Revelli, 2011;Slegten et al, 2019) mean that the greater the diversity of gender within municipal government teams, the higher the institutional financial sustainability, due to lower levels of debt.…”
Section: Findings and Discussionsupporting
confidence: 77%
“…A greater number of female political representatives would lead to higher attention given to policies of concern to women (Meier & Funk, 2017;Phillips, 1998;Smith, 2014). The literature, by and large, suggests that the different preferences of male vs female political leaders lead to differences of public policies on expenses and taxes (see Alozie & McNamara, 2010;Bhalotra & Clots-Figueras, 2014;Martínez-Córdoba et al, 2022;Cabaleiro-Casal & Buch-Gómez, 2018, 2020bFerreira & Gyourko, 2014;Fox & Schuhmann, 1999;Funk & Gathmann, 2015). Specifically, research has highlighted that female politicians have a greater preference for higher public expenditures, primarily on public policies oriented towards social welfare than do male leaders.…”
Section: Gender Diversity In Municipal Governments and Budgetary Solv...mentioning
confidence: 99%
“…Rent is a measure of municipal income. 8 Debt, measured as outstanding debt at the end of the fiscal year, controls for the municipality's level of indebtedness, which is relevant in the Spanish budget process (Cabaleiro-Casal and Buch-Gómez, 2018;Cabaleiro-Casal and Buch-Gómez, 2021;Balaguer-Coll and Ivanova-Toneva, 2021). Debt and Rent are expressed in per cent of total spending.…”
Section: Identification and Datamentioning
confidence: 99%